Pengembangan Media Pembelajaran Game Teka Teki Silang Materi Beriman Kepada Allah dan Rasul-Nya Kelas IV Di Sekolah Dasar - Oktaria, Nisca; Arni, Yusni; Triani, Isnatun; Aulia, M. Sulton; Pradida, Reyhan (ALACRITY : Journal of Education, 2024)
To increase students' interest and motivation in studying religious content, learning materials based on crossword games have been developed for grade IV elementary school which includes faith in Allah and His Messenger. From design to classroom implementation, the process of creating educational media is discussed in this article. Research findings show that the use of crossword game-based learning resources can improve students' understanding and memory of lesson material. In addition, these educational resources can support the growth of students' critical and collaborative thinking abilities.